Singleplex real-time PCR and duplex PCR platform for the rapid detection of hypervirulent Klebsiella pneumoniae - Wang, Jiaqi; Wu, Yishuai; Zhao, Liying; Xing, Mengran; Huang, Yangyang; Peng, Shengjie; Xu, Chunyan; Yao, Hong; Li, Chenglong; Du, Xiang-Dang (Frontiers in Veterinary Science, 2025)
Hypervirulent Klebsiella pneumoniae (HvKP) is a notorious zoonotic pathogen that poses a significant threat to public health, as it can cause severe infections with high morbidity and mortality among young and healthy individuals. Commonly, a positive string test is primarily used to identify HvKP strains, but which is laborious and time-consuming. A rapid assay to identify HvKP is needed for public health personnel to track the spread of these strains and provide timely efforts for their control. Given this context, rapid SYBR Green I-based singleplex real-time PCR assays were developed for defining HvKP on the basis of the biomarkers iroB, iucA, peg-344 and plasmid-borne rmpA, respectively. These four singleplex PCR assays all displayed a high degree of linearity (R2>0.99) in the range of 104 to 109 cfu/mL, and the limit of detection (LOD) was 103 cfu/mL, which was equivalent to 10 cfu/reaction. To improve the efficiency and reduce the cost of diagnostic testing, SYBR Green I-based duplex PCR melting curve assays were developed with average melting temperatures of 85.0, 87.5, 76.0 and 78.5°C for iroB, iucA, peg-344 and plasmid-borne rmpA, respectively. The LODs for the developed duplex PCRs for iroB/peg-344, iucA/peg-344 and iucA/rmpA combination were 104 cfu/mL (that was 102 cfu/reaction), 104 cfu/mL (that was 102 cfu/reaction) and 105 cfu/mL (that was 103 cfu/reaction), respectively. High specificity was shown when other bacterial pathogens were detected in this study. These assays could be used as rapid, sensitive and specific diagnostic tools for the practical identification of HvKP strains.